Experimental investigation work on a solar cavity collector. (2023) - Lakshmipathy, B.; Kajavali, A.; Krishnan, S.; Senthil kumar, M.; Sivakumar, K.
Abstract: Solar collector is a device that converts the solar radiation into some useful heat energy. The conventional solar collector often used globally to heat water is a Flat Plate Solar Collector (FPC) configuration. Solar Cavity Collector (SCC) is a newly designed modern version of an FPC. In order to improve the performance characteristics of FPC, it has been modified with necessary design changes and termed as cavity collector. Cavity type collectors are more familiar with Fresnel and concentrating type collectors but they have been implemented for the development of FPC. A tubular absorber cum receiver which is 6.35 mm in radius with black colour paint coated onto it has been concentrically positioned in the cylindrical contour. SCC comprises combinations of 5 individual cavities and receivers. Five such cavities and receivers are fabricated at first, and they have been placed concentrically in a 50 × 50 square shaped metal enclosure box. A performance test has been conducted on SCC with the following parameters:(1) Receiver materials of both aluminium and copper;(2) changing the mode of flow as parallel and serpentine types;(3) angle of tilt of the whole setup of SCC;(4) SCC has been packed with metal scrap chips and pebbles bed;(5) cavity cover materials of both mild steel (MS) and galvanized iron (G.I) have been tested. The result shows that the usage of copper as a receiver material performs better than the aluminium. SCC with the usage of pebbles has an improvement in energy transfer of about 3 %. The methodology with improved heat transfer characteristics can be achieved by SCC and it can be effectively used during cloudy and partly cloudy days where the intermittence in solar energy is inexorable.